Hubungan locus of control dengan orientasi kewirausahaan mahasiswa yang berbasis online pada mahasiswa wirausaha - Sarah Khoerunisa; Tutut Chusniyah (Universitas Negeri Malang, 2021)
This study aims to (1) to determine the locus of control of the Brawijaya University students who are running online businesses (2) to identify their entrepreneurial orientation of the Brawijaya University students who are running online businesses (3) to observe the correlate between locus of control and entrepreneurial orientation associated to the online businesses of the students of Brawijaya University. Samples in this study were 101 members of students' business UKM of Brawijaya University Malang. Test of hypothesis was using analysis technique of Pearson Product Moment. The results of this study indicate that (1) most of college students who do business online have an internal locus of control, (2) most of college students who do business online have levels entrepreneurial orientation is low, (3) there is no correlation between entrepreneurial orientation and of locus of control in Brawijaya University students who are running online businesses. Penelitian ini bertujuan untuk (1) untuk mengetahui gambaran locus of control mahasiswa yang berbisnis online pada Mahasiswa Wirausaha Universitas Brawijaya, (2) untuk mengetahui gambaran orientasi kewirausahaan mahasiswa yang berbisnis online pada Mahasiswa Wirausaha Universitas Brawijaya, (3) untuk mengetahui hubungan antara locus of control dengan orientasi kewirausahaan mahasiswa yang berbisnis online pada Mahasiswa Wirausaha Universitas Brawijaya. Sampel dalam penelitian ini sebanyak 101 anggota UKM Mahasiswa Wirausaha Universitas Brawijaya Malang. Uji hipotesis menggunakan teknik analisis korelasi Pearson Product Moment. Hasil penelitian ini menunjukkan bahwa (1) sebagian besar mahasiswa yang berbisnis online mempunyai locus of control internal (2) sebagian besar mahasiswa yang berbisnis online mempunyai orientasi kewirausahaan yang rendah (3) tidak terdapat hubungan antara locus of control dengan orientasi kewirausahaan pada mahasiswa yang berbisnis online di Mahasiswa Wirausaha Universitas Brawijaya Malang.